Molecular and multi-scale modelling methods of polymer device degradation - Han, X.
This chapter presents molecular models that can simulate microscopic polymer degradation behaviours instead of using phenomenological governing equations. Polymer details such as molecular weight distribution, end chain scission and random chain scission rates, and the copolymer ratio can be taken into account in the molecular models using the Kinetic Monte Carlo (KMC)method. A multi-scale model of the device degradation is also introduced in this chapter combining the molecular models and the macroscopic small molecule diffusion. The multi-scale model enables investigation of how local polymer properties affect bulk qualities over the entire device, which was not previously possible. In this chapter, the multi-scale model is also utilized to analyse experimental data, and correlations between detailed polymer properties and degradation rate are finalized. © 2015 Elsevier Ltd. All rights reserved.
Keywords: DEGRADATION; DIFFUSION; KINETIC MONTE CARLO (KMC); MODELLING; MOLECULAR MODELS; MULTI-SCALE